PROFITABILITAS DAN LEVERAGE TERHADAP NILAI PERUSAHAAN DENGAN HARGA SAHAM SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN TRANSPORTASI YANG TERDAFTAR DI BEI TAHUN 2020-2023 - Amalia, Risky Sofiatul; Wahyuni, Ika; Widaninggar, Nanda (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
The Indonesian capital market, namely the Indonesia Stock Exchange (IDX), plays an important role as a means for companies to obtain funding and for investors in investing capital. The stock investment offers potential profits in the form of dividends and capital gains, both of which reflect investor perceptions of company performance. The company value is an important indicator in assessing the success of a company, which can be influenced by various financial factors such as Profitability and Leverage. Transportation sector companies are one of the strategic sectors that support national economic connectivity and have experienced significant dynamics during the COVID-19 pandemic and its recovery. There are 55 transportation companies listed on the IDX during the 2020-2023 periods. This study aims to analyze and test the Effect of Profitability and Leverage on Company Value with Stock Price as a moderating variable. The sampling technique is done by purposive sampling method. The data analysis method and hypothesis testing of this research used Structural Equation Analysis – Partial Least Square (PLS-SEM). The results of hypothesis testing using the Smart PLS 3.0 application, show that Profitability has a positive but insignificant effect on Company Value, Leverage has a positive but insignificant effect on Company Value, Stock Price has a positive but insignificant effect in moderating Profitability on Company Value, Stock Price has a positive but insignificant effect in moderating Leverage on Company Value.